2010
DOI: 10.1359/jbmr.090729
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene analysis of femoral neck trabecular and cortical volumetric bone mineral density in older men

Abstract: In contrast to conventional dual-energy X-ray absorptiometry, quantitative computed tomography separately measures trabecular and cortical volumetric bone mineral density (vBMD). Little is known about the genetic variants associated with trabecular and cortical vBMD in humans, although both may be important for determining bone strength and osteoporotic risk. In the current analysis, we tested the hypothesis that there are genetic variants associated with trabecular and cortical vBMD at the femoral neck by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…More recently WNT3A, known to affect osteoblast differentiation (Monroe et al 2012), was found to be associated with BMD in Australian postmenopausal women (Sims et al 2008); a meta-analysis combining five GWAS identified a large linkage disequilibrium (LD) block encompassing LRP4 associated with femoral neck and lumbar spine BMD (Styrkarsdottir et al 2008). It has also been suggested that LRP6 polymorphisms influence BMD (Sims et al 2008;van Meurs et al 2008); however, the results have been conflicting (Mencej-Bedrac et al 2009;Yerges et al 2010). Recently, Estrada et al (2012) performed a metaanalysis including data from 17 genome-wide association studies of European and East Asian ancestry, highlighting the critical role of several genes (WNT16, LRP5, DKK1, LRP4, WNT4.…”
Section: Introductionmentioning
confidence: 99%
“…More recently WNT3A, known to affect osteoblast differentiation (Monroe et al 2012), was found to be associated with BMD in Australian postmenopausal women (Sims et al 2008); a meta-analysis combining five GWAS identified a large linkage disequilibrium (LD) block encompassing LRP4 associated with femoral neck and lumbar spine BMD (Styrkarsdottir et al 2008). It has also been suggested that LRP6 polymorphisms influence BMD (Sims et al 2008;van Meurs et al 2008); however, the results have been conflicting (Mencej-Bedrac et al 2009;Yerges et al 2010). Recently, Estrada et al (2012) performed a metaanalysis including data from 17 genome-wide association studies of European and East Asian ancestry, highlighting the critical role of several genes (WNT16, LRP5, DKK1, LRP4, WNT4.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in a relatively large study of men, no significant association was observed between these three genes and volumetric BMD at the femoral neck and lumbar spine (LS) (34) or trabecular and cortical volumetric BMD at the femoral neck. (35) Nevertheless, recently, SNPs located near RANKL, (36) RANK, (37) and OPG (36,38) also have been associated with BMD in genome-wide association studies (GWAS).…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric BMD (vBMD) for both compartments is heritable, with heritability estimates of 17% to 42% for cortical vBMD and 59% to 73% for trabecular vBMD [29][30][31] . In a study aiming to investigate the candidate gene of femoral neck trabecular and cortical vBMD in older men by genotyping 4608 tagging and potentially functional SNPs in 383 bone metabolism candidate genes in 822 Caucasian men aged 65 years or older from the Osteoporotic Fractures in Men Study (MrOS), the results indicated that rs6127983 of BMP7 was robustly associated with trabecular vBMD [32] . Osteoporotic fracture is an outcome of low-trauma to bone of compromised strength, and its incidence is increased by various risk factors.…”
Section: Discussionmentioning
confidence: 99%